Unity in Diversity: Common Thread in the Factors that Drive Success of MultiSponsor Loyalty Programs - Shinha, Shameek (IE University, 2019)
Resumen: We had access to 10,000 of the coalition loyalty programs most active customers for the year 2015. Within that time window, these customers had 1,731,557 transactions across different partners (5,387 shopping points) under multiple product categories, received 4,227,467 promotional campaigns, responded to offers 1,101,597 times, and had redeemed their due rewards 56,130 times. Objetivo de la Investigación: the strategic management of customers by identifying tactical decision variables across the different information dimensions, such that the firms can optimize the success of the multi-sponsor loyalty program while simultaneously proving incentives to partners for active participation.
Keywords: Strategic management; Customer; Tactical decision variables; Multi-sponsor loyalty program; Incentives